2021
DOI: 10.17221/544/2020-pse
|View full text |Cite
|
Sign up to set email alerts
|

Biochar remediation of soil: linking biochar production with function in heavy metal contaminated soils

Abstract: The focus of this study is on the soil physicochemical, biological, and microbiological processes altered by biochar application to heavy metal (HM) contaminated soils. The aim is to highlight agronomical and environmental issues by which the restorative capacity of biochar might be developed. Literature shows biochar can induce soil remediation, however, it is unclear how soil processes are linked mechanistically to biochar production and if these processes can be manipulated to enhance soil remediation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 134 publications
0
8
0
Order By: Relevance
“…Many studies have demonstrated that biochar addition reduces soil acidity and increases soil pH through proton consumption reactions in acidic soils (Mehmood et al, 2018). This increase in soil pH can decrease HMs mobility in soil through mechanisms such as adsorption, surface complexation precipitation, and electrostatic interaction (Taraqqi‐A‐Kamal et al, 2021; Wei et al, 2022). In our study, the pH and total Pb content in soil increased significantly with the amendment of biochar (Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that biochar addition reduces soil acidity and increases soil pH through proton consumption reactions in acidic soils (Mehmood et al, 2018). This increase in soil pH can decrease HMs mobility in soil through mechanisms such as adsorption, surface complexation precipitation, and electrostatic interaction (Taraqqi‐A‐Kamal et al, 2021; Wei et al, 2022). In our study, the pH and total Pb content in soil increased significantly with the amendment of biochar (Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…7,15,89 It is important though, to predict the long-term behaviour of soil amendments even if their effects are positive so that we can make a sustainable choice of amendment and application rate both in terms of environmental and financial efficiency. 14 The layered design that was used in this study could be a simulation of field application of soil amendments in the form of reactive barriers that are not mixed with the soil and could potentially be later removed from it. In addition, our results can assist in a future enhanced experimental design in which the sorbent layer will be more reactive.…”
Section: Environmental Implications Of Long-term Effects Of Soil Amen...mentioning
confidence: 99%
“…101 Long-term studies on the efficiency of BC and the changes it provokes in the soil are still scarce, and the mechanisms involved are not yet fully explained. 14 Although a wide range of pyrolysis temperatures (400-700 °C) has been reported to produce biochar efficient for the immobilisation of Zn and Pb, 70 high temperatures (i.e., 700 °C) generally result in limited functional groups on the surface of BC and could lead to a decrease in the metal removal efficiency of BC. 102 In addition, there is evidence that the release of contaminants in untreated soil is more likely when nonspecific adsorption takes place, especially in the case of multiple element contamination.…”
Section: Environmental Implications Of Long-term Effects Of Soil Amen...mentioning
confidence: 99%
See 2 more Smart Citations